DEVELOPMENT OF STANDARD OPERATING PROCEDURES FOR WALKING FOOT SEWING MACHINE NEEDLE REPLACEMENT BASED ON THE DECLINE OF STITCH QUALITY IN LEATHER PRODUCT MANUFACTURING AT SMALL AND MEDIUM INDUSTRY - Wawan Budi Setyawan (Politek ATK Yogyakarta Press, 2026)
Leather product manufacturing in Small and Medium Enterprises (SMEs) still relies heavily on operator experience in determining the replacement interval of sewing machine needles. Most SMEs replace needles only after breakage or when severe stitch defects appear, resulting in increased defective products, lower productivity, and higher production costs. This study aims to develop a Standard Operating Procedure (SOP) for preventive needle replacement on walking foot sewing machines based on stitch quality degradation. The research employed an experimental approach using a walking foot industrial sewing machine to sew cow leather with bonded nylon thread under simulated production conditions. Needle operating time was varied at 0, 8, 16, 24, and 32 hours. Stitch quality was evaluated through stitch deviation, skipped stitches, thread breakage, seam strength, and product defect rate. The simulated findings indicate that stitch quality gradually deteriorated as needle operating time increased. Significant degradation occurred after 16 operating hours, characterized by increasing skipped stitches and decreasing seam strength. Based on these findings, an SOP recommending preventive needle replacement every 16 operating hours was developed to maintain production quality and reduce defects in leather manufacturing SMEs. The proposed SOP is expected to improve product consistency, production efficiency, and maintenance practices.